Farmers' Implementation of Integrated Pest Management (Ipm) Methods for The Onion Crop in The Qutour District- Gharbiah Governorate - Abdallah, Hamza Hamed; Elkawa, Alaa Mohamed; Abdelwahab, Saber Mohamed (Journal of agricultural, environmental and veterinary sciences, 2022)
This research aimed to identify the level of farmers' implementation of integrated pest management (IPM) methods for the onion crop in the Qutour district- Gharbiah governorate, determining the contribution of independent variables which have a correlation relationship in explaining the variation in the degree of their implementation of these methods, identifying the indicative methods preferred by the respondents in order to obtain their knowledge in this field, and identifying the reasons for not implementing these methods.This research was conducted in Gharbiah Governorate, as it is one of the largest governorates of the Republic for the cultivation of the onion crop (49981 Faddans), and with the same criterion, Qutour district (10,235 Faddans) was selected. From it, three villages were selected randomly; they were the villages of Abu Gendi, Samla, and Al-Haramlah. This was followed by selection of a regular random sample represents 10% of the farmers in three selected villages. So the sample size was amounted to 179 respondents. The statistical methods which used in data analysis and presentation of the results were: frequencies, percentages, arithmetic mean, standard deviation, Pearson's simple correlation coefficient, model of multiple regression correlation analysis (step-wise).The most important results were as follows:1- 60.3% of the respondents have an moderate level of implementation of recommendations related to agricultural control, 77.7% of them have an moderate level of implementation of recommendations related to chemical control, about 51% of them have an moderate level of implementation of recommendations related to mechanical control, and approximately 70% of them have a low level of implementation of the recommendations related to biological control.2- The most important variables contributed in explaining the variation in the dependent variable were: the number of years of experience in the cultivation of the onion crop, the educational status of the respondent, the average production of the Faddan of the onion crop, the degree of exposure to agricultural information sources, satisfaction with the economic return from the cultivation of the onion crop, the degree of Availability of extension services, purpose of cultivation, and Attitude towards agricultural extension.3-The most methods preferred by the respondents were: field and office visits, panels, extension meetings and extension fields, while the least ranked ways in the respondents’ preference were extension publications, the Internet, and home visits.4-It was found that the respondents’ lack of knowledge with these recommendations and the high prices of their application, low onion prices, and low role of the agricultural extension in applying these recommendations were the most important reasons for not implementing these methods.
Keywords: integrated control; agricultural pests; onion crop; Qotour Center; Gharbia Governorate